Going public : civic and community engagement - Fitzgerald, Hiram E.; Primavera, Judy (Transformations in higher education., 2013)
The terms "civic engagement" and "community engagement" have various definitions, but they are united by the sense that individuals who are civically engaged not only are concerned about the quality of life in their communities, but also take action to improve conditions for the common good. In the United States, to be civically engaged means to actively participate in a civil democratic society. This book examines programs related to civic engagement and the ways in which faculty and students participate in communities in order to improve them. Engagement scholarship is a scholarship of action, a scholarship of practice that takes place both in and with the community. Within the framework of this new scholarship, the mission of the academy does not begin and end with intellectual discovery and fact-finding. Rather, the academy joins forces with the community, and together they use their knowledge and resources to address pressing social, civic, economic, and moral problems. Each chapter in this book tells a unique story of community engagement and the scholarship of practice in a diverse range of settings, documenting successes and failures, the unintended consequences, and the questions yet to be answered.